PLACE IDENTITY AMONG NATIVE MINORITIES: LESSONS FROM ARABS IN ISRAEL. Issue 2 (15th March 2022) - Shdema, Ilan; Martin, Deborah
Abstract: This study addresses place identity among native minorities by focusing on the Arabs in Israel. It follows a recent trend in geography—the environmental-psychology approach to place identity—which focuses on the identity of individuals rather than the identity of places commonly emphasized in human geography. The study draws on mixed methods: 25 in-depth interviews with residents of Arab localities, in addition to questionnaires administered to both Arabs (210) and Jews (100) serving as a comparison group. Native minority members in this study have emphasized place identity as rooted in multilayered memories in situ, the clan-based social structure, and tensions with the government. These issues are discussed in the contexts of majority-minority relations and settler colonialism and nativism.